2023
DOI: 10.3390/diagnostics13040728
|View full text |Cite
|
Sign up to set email alerts
|

Utility and Limitations of Fine-Needle Aspiration Cytology in the Diagnosis of Lymphadenopathy

Abstract: Background: Fine needle aspiration cytology (FNAC) is a valuable tool for evaluating lymphadenopathy. The purpose of this study was to assess the reliability and effectiveness of FNAC in the diagnosis of lymphadenopathy. Methods: Cytological characteristics were evaluated in 432 patients who underwent lymph node FNAC and follow-up biopsy at the Korea Cancer Center Hospital from January 2015 to December 2019. Results: Fifteen (3.5%) of the four hundred and thirty-two patients were diagnosed as inadequate by FNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…In the paper by Hwa Jeong Ha et al, FNAC was found to have a sensitivity of 97.8%, specificity of 97.5%, PPV of 98.7% and NPV of 97.7% compared to histopathological analysis. The overall accuracy was 97.7% ( 10 ). For metastatic carcinoma, our results were in good agreement with the cytological diagnosis rate in the literature for metastatic carcinoma in lymph nodes, which was 90 to 100% ( 11 , 12 ).…”
Section: Discussionmentioning
confidence: 98%
“…In the paper by Hwa Jeong Ha et al, FNAC was found to have a sensitivity of 97.8%, specificity of 97.5%, PPV of 98.7% and NPV of 97.7% compared to histopathological analysis. The overall accuracy was 97.7% ( 10 ). For metastatic carcinoma, our results were in good agreement with the cytological diagnosis rate in the literature for metastatic carcinoma in lymph nodes, which was 90 to 100% ( 11 , 12 ).…”
Section: Discussionmentioning
confidence: 98%
“…Ha et al initially introduced the technique of FNAC. FNAC has become widely used as a diagnostic tool for rapid evaluation of mainly superficial lesions [ 8 ]. Lymphadenopathy refers to lymph nodes exhibiting abnormalities in size, consistency, or number.…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosed cases were reactive lymph node at 13 (25.0%), TB at four (7.7%), lymphoma at 16 (30.8%), and malignancy at four (7.7%). Another previous study reported that tru-cut biopsy had a sensitivity of 68.42%, a specificity of 83.33%, a PPV of 92.86%, an NPV of 45.45%, and an accuracy rate of 72% [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…A thorough history and physical examination should be implemented in diagnosing CLA; however, clinical assessment alone is not enough because the patient’s presentation can mimic other conditions [ 4 ]. Fine-needle aspiration cytology (FNAC) is the initial step in diagnosing lymphadenopathy due to its simplicity, rapid availability of results, and minimal complications [ 5 ].…”
Section: Introductionmentioning
confidence: 99%